Hubungan Daya Tarik Pesan Iklan Di Jejaring Sosial Instagram Dengan Minat Membeli - Fatah, Ian; , Dr. Eny Purwandari, M.Si (2016)
Indonesian lifestyle shopping today makes everything is instant. With the era of the all-round technology and online, will make things even easier and faster. Lots of shopping trends emerging in Indonesia society, such as from discounts given just before midnight until the trend today is shopping via the internet or often called online shopping. Through the Internet, the Indonesian people no longer need to go to the store, no longer need to queue up, simply by smartphone Indonesian society has been able to purchase a good or service. Subjects of this study is the active user and make buying and selling online at Instagram that totaling 260 subjects. Sampling using quota sampling that sampling occurs by setting a certain amount as a target that must be fulfilled in the sampling of the population (especially the infinite or unclear), then the benchmark number of the researchers took samples of arbitrary origin qualify as a sample of the population. The results showed that there was a significant positive correlation between the appeal of advertising messages on the social networking to buying interest. This positive relationship of this study illustrate that the stronger the appeal of advertising messages on social networks, the higher interest on consumer buying and conversely the weaker the appeal of advertising messages on social network Instagram, the lower the interest to buy of the consumer. The appeal of advertising messages on social networks including one of the factors that can determine consumer buying interest, amounted to 34.57%.